2013
DOI: 10.3389/fgene.2013.00178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating statistical analysis models for RNA sequencing experiments

Abstract: Validating statistical analysis methods for RNA sequencing (RNA-seq) experiments is a complex task. Researchers often find themselves having to decide between competing models or assessing the reliability of results obtained with a designated analysis program. Computer simulation has been the most frequently used procedure to verify the adequacy of a model. However, datasets generated by simulations depend on the parameterization and the assumptions of the selected model. Moreover, such datasets may constitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…Robles et al (2012) likewise compared 3 methods and found inflated type I error rates for some methods and conservative performance from others. Reeb and Steibel (2013) compared 3 methods using "plasmodes" (resampled data) and found inflated type I error rates for small significance levels. Guo, Li, Ye, and Shyr (2013) compare 6 methods and conclude that all "suffer from over-sensitivity".…”
Section: Discussionmentioning
confidence: 99%
“…Robles et al (2012) likewise compared 3 methods and found inflated type I error rates for some methods and conservative performance from others. Reeb and Steibel (2013) compared 3 methods using "plasmodes" (resampled data) and found inflated type I error rates for small significance levels. Guo, Li, Ye, and Shyr (2013) compare 6 methods and conclude that all "suffer from over-sensitivity".…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analysis (PCA) of the twelve liver transcriptomes was applied to examine the contribution of each transcript to the separation of the classes3435. Then, fastq formatted reads from the two diploid parents and two hybrid offspring were mapped to the reference genome using TopHat23637.…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptome de novo assembly was carried out with a short-reads assembly program (Trinity) [54], using three independent software modules called Inchworm, Chrysalis, and Butterfly. Principal component analysis (PCA) of nine liver transcriptomes was applied to examine the contribution of each transcript to the separation of the classes [55, 56] (Additional file 9). …”
Section: Methodsmentioning
confidence: 99%